2013
DOI: 10.1097/jto.0b013e318287c3eb
|View full text |Cite
|
Sign up to set email alerts
|

New IASLC/ATS/ERS Classification and Invasive Tumor Size are Predictive of Disease Recurrence in Stage I Lung Adenocarcinoma

Abstract: : The new International Association for the Study of Lung Cancer, American Thoracic Society, and European Respiratory Society ADC classification and invasive tumor size are very useful predictors of recurrence of stage I ADCs in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 11 publications
(13 reference statements)
7
84
0
Order By: Relevance
“…SOL/MIP predominant pattern was associated with unfavorable prognosis for higher recurrence and death possibility, in accordance with previous studies (Hung et al 2013; Li et al 2009;Russell and Wright 2016;Xu et al 2015;Yanagawa et al 2013;Yoshizawa et al 2011;Zhang et al 2013). Patients with SOL/MIP predominant pattern could benefit from adjuvant chemotherapy for a better DFS after complete resection.…”
Section: Discussionsupporting
confidence: 79%
“…SOL/MIP predominant pattern was associated with unfavorable prognosis for higher recurrence and death possibility, in accordance with previous studies (Hung et al 2013; Li et al 2009;Russell and Wright 2016;Xu et al 2015;Yanagawa et al 2013;Yoshizawa et al 2011;Zhang et al 2013). Patients with SOL/MIP predominant pattern could benefit from adjuvant chemotherapy for a better DFS after complete resection.…”
Section: Discussionsupporting
confidence: 79%
“…Prior studies have shown outcomes of 100% RFS after surgical resection for AIS and MIA, and among the five subtypes of adenocarcinoma, lepidic adenocarcinoma showed the most favorable prognosis (14,15). Some reports also determined that the degree of lepidic pattern in a tumor was related to disease prognosis, where greater than 50% lepidic pattern was a favorable prognostic indicator in cases of invasive adenocarcinoma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In these series, lower grade tumours (such as lepidic predominant) have been shown to be associated with a lower risk for recurrence, while those with higher grade tumours (such as micropapillary, invasive mucinous adenocarcinoma and solid predominant tumours) had worse disease-free and overall survival [9]. This prognostic ability remains significant in multivariate analyses that include factors such as age, stage and resection margin status, among other covariates, acting as an independent predictor of disease-free and overall survival [6,[10][11][12]. However, in some series, its prognostic ability has been weaker [13].…”
Section: @Erspublicationsmentioning
confidence: 86%